Stable isotope evidence from formalin–ethanol-preserved specimens indicates dietary shifts and increasing diet overlap in Lake Victoria cichlids - Mary A. Kishe-Machumu; Jacco C. van Rijssel; Amanda Poste; Robert E. Hecky; Frans Witte (Hydrobiologia, 2017)

Climatic variability in combination with eutrophication drives adaptive responses in the gills of Lake Victoria cichlids - Jacco C. van Rijssel; Robert E. Hecky; Mary A. Kishe-Machumu; Saskia E. Meijer; Johan Pols; Kaj M. van Tienderen; Jan D. Ververs; Jan H. Wanink; Frans Witte (Oecologia, 2016)

Can differential resurgence of haplochromine trophic groups in Lake Victoria be explained by selective Nile perch, Lates niloticus (L.) predation? - Mary A. Kishe-Machumu; Tanja Voogd; Jan H. Wanink; Frans Witte (Environmental Biology of Fishes, 2015)

Cichlid species diversity in naturally and anthropogenically turbid habitats of Lake Victoria, East Africa - Frans Witte; Ole Seehausen; Jan H. Wanink; Mary A. Kishe-Machumu; Marjolein Rensing; Tijs Goldschmidt (Aquatic Sciences, 2013)

Adaptive responses in resurgent Lake Victoria cichlids over the past 30 years - Jacco C. van Rijssel; Frans Witte (Evolutionary Ecology, 2013)

The diet of Nile perch, Lates niloticus (L.) after resurgence of haplochromine cichlids in the Mwanza Gulf of Lake Victoria - Mary A. Kishe-Machumu; Frans Witte; Jan H. Wanink; Egid F. B. Katunzi (Hydrobiologia, 2012)

Transcriptome analysis of the response to chronic constant hypoxia in zebrafish hearts - Ines J. Marques; Jelani T. D. Leito; Herman P. Spaink; Janwillem Testerink; Richard T. Jaspers; Frans Witte; Sjoerd van den Berg; Christoph P. Bagowski (Journal of Comparative Physiology B, 2008)

The invasion of an introduced predator, Nile perch (Lates niloticus, L.) in Lake Victoria (East Africa): chronology and causes - Kees (P.C.) Goudswaard; Frans Witte; Egid F. B. Katunzi (Environmental Biology of Fishes, 2007)

The Shrimp Caridina nilotica in Lake Victoria (East Africa), Before and After the Nile Perch Increase - Kees (P.C.) Goudswaard; Frans Witte; Jan H. Wanink (Hydrobiologia, 2006)

Camouflaged invasion of Lake Malawi by an Oriental gastropod - MARTIN J. GENNER; ELLINOR MICHEL; DIRK ERPENBECK; NICOLE DE VOOGD; FRANS WITTE; JEAN‐PIERRE POINTIER (Molecular Ecology, 2004)
In this study we report the first animal invasion, to our knowledge, into Lake Malawi. The colonizer is a non‐native morph of the gastropod Melanoides tuberculata that differs substantially in external shell characters from co‐occurring indigenous forms. However, because the species possesses extensive within‐Africa geographical variation in shell morphology, it was unclear whether the invasion was range expansion of a native African morph, or a colonization from elsewhere. Mitochondrial DNA sequences indicate a southeast Asian origin for the invader, suggesting that shell variation found among indigenous allopatric populations camouflaged an intercontinental invasion.

Diel vertical migration of major fish-species in Lake Victoria, East Africa - Kees Goudswaard; Jan H. Wanink; Frans Witte; Egid F.B. Katunzi; Michiel R. Berger; David J. Postma (Hydrobiologia, 2004)

On research on tilapiine and haplochromine cichlids - Frans Witte (Hydrobiologia, 2002)

Eco-hydrology: Groundwater flow and site factors in plant ecology - Frans Klijn; Jan-Philip M. Witte (Hydrogeology Journal, 1999)

Patterns of the Remnant Cichlid Fauna in Southern Lake Victoria - Ole Seehausen; Frans Witte; Egid F. Katunzi; Jan Smits; Niels Bouton (Conservation Biology, 1997)
During the years 1984–1987 Lake Victoria in East Africa experienced what is probably the largest mass extinction of contemporary vertebrates. Within a decade about 200 endemic species of haplochromine cichlids disappeared. The extinctions that occurred in the 1980s have been documented predominantly on species of offshore and sub‐littoral waters in the Mwanza Gulf of southern Lake Victoria. Although the littoral fauna of southern Lake Victoria had not been examined in detail, their diversity seemed less affected by the changes in the ecosystem. We give results of the first comprehensive inventory of the littoral cichlid fauna in southern Lake Victoria and discuss its conservation status. We also report on new developments in the sub‐littoral fauna after 1990. More than 50 littoral and 15 sub‐littoral stations were sampled between the years 1991 to 1995. Of the littoral stations, 34 were sampled for the first time. One hundred sixty three species of haplochromines were collected. Of these, 102 species were previously unknown. About two thirds of them live in rocky areas that were sampled for the first time. Littoral rocky habitats harbored the highest diversity. Since 1990, however, 13 more species disappeared from established sampling stations in littoral habitats. Fishing practices, spreading of exotic fishes, water hyacinth, and eutrophication are considered important threats to the littoral fauna. Also in the upper sub‐littoral the number of species declined further. On deeper sub‐littoral mud bottoms individual and species numbers increased again, although they are nowhere close to those found before the Nile perch (Lates niloticus) upsurge. This fauna differs from the well studied pre‐Nile perch fauna. At well‐established sampling stations, the sub‐littoral zone is dominated by previously unknown species, and some known species have performed dramatic habitat shifts.

The catfish fauna of Lake Victoria after the Nile perch upsurge - Kees Goudswaard & Frans Witte (Environmental Biology of Fishes, 1997)